Undesirable river biofilms: the composition, environmental drivers, and occurrence of sewage fungus - Exton, Benjamin; Hassard, Francis; Medina, Angel; Grabowski, Robert C. (Elsevier, 2024)
Sewage fungus is a classic bioindicator of organic pollution in streams and rivers. However, it has received limited scientific interest in recent decades, despite persistent occurrence in lotic ecosystems. The aim of this review is to provide an up-to-date assessment of sewage fungus, its composition and structure, and the environmental factors that influence its growth to support future research and mitigation interventions. We advocate for the term “undesirable river biofilm” (URB) to more accurately characterise the composition, location, and environmental consequences of sewage fungus. These filamentous or gelatinous growths found on the banks and beds of flowing watercourses are composed predominantly of bacteria, not fungi. Based on modern genomic analyses, we now know that URBs are composed of a diversity of microbial taxa, including those that have long been associated with sewage fungus (e.g. Sphaerotilus, Beggiatoa, and Zoogloea) and newer associated taxa (e.g. Rhodoferax and Thiothrix). While organic pollution is generally considered the main trigger, this review highlights the importance of other environmental factors, such as water velocity, river substrate, pollutant composition and loading, and shading, in the occurrence and persistence of URBs. To illustrate the widespread and continued presence of URBs in rivers, environmental surveillance data for England's rivers were analysed. Between 2000 and 2020, environment officers documented 6,025 occurrences of URBs as part of a wider water quality incident reporting programme. Thus, URBs persist even in countries with stringent water quality standards and comprehensive wastewater infrastructure, suggesting they may continue to be a significant issue globally, despite limited public or scientific focus. We argue that in addition to tackling point discharge of organic pollutants, greater emphasis should be placed on understanding the impact of intermittent and diffuse pollution and altered environmental conditions on river ecosystems. To safeguard river ecosystems, a holistic approach is needed that considers pollution in combination with wider river functioning (e.g. river hydrology, geomorphology, biogeochemical processing, and riparian zones) and climate change. Future areas for study into the URB phenomenon are suggested, including more comprehensive monitoring of URBs specifically and river biofilm health generally.
Keywords: Sphaerotilus natans; Periphyton; Organic pollution; Water quality; Ecological impacts; Bioindicator